A new desulfation process of spent lead paste via cyclic utilization of CO2–NH3·H2O. (15th May 2022) - Hua, Chunyu; Pan, Junqing; Li, Zhiyu; Wang, Keyu; Sun, Yanzhi; Li, Dan; Li, Tian
Abstract: The costly desulfation processes have severely restricted the development and industrial application of hydrometallurgy lead recovery process. In this work, new high efficiency and value-added desulfation method of the spent lead paste is proposed. The new route consists of three sections as follows: (1) Desulfation of spent lead paste by ammonium carbonate; (2) Regeneration of ammonium carbonate through calcium hydroxide sulfuration and ammonia carbonation; (3) Lead carbonate decomposition to obtain the product lead oxide and CO2 to construct a high efficiency and value-added desulfation method of the spent lead paste. The regenerated ammonium carbonate filtrate is re-used in the next batch desulfation process in order to realize a green and sustainable process. For the tests of 5 cycles, the optimal average conversion rate of calcium hydroxide sulfation is up to 88.2% and the desulfation rate of lead paste is above 98.7% as well ammonium ions concentration maintains stable all the way. This work put forwards calcium hydroxide as an inexpensive desulfurizer via "ex-situ nucleation process (ESNP)" and "CO2 –NH3 ·H2 O" strategy, providing a cleaner and more economical routes to recover PbO from lead-acid batteries. The cost calculation and technical analysis indicate this new strategy is economical, efficient, and high value-added. Graphical abstract: Image 1 Highlights: Hydrated lime is proposed as the value-added desulfurizer for spent lead paste. A new ex-situ nucleation process realizes the high utilization rate of hydrated lime. The desulfation rate of spent lead paste is up to 98.7%. The optimal average conversion rate of hydrated lime sulfuration is 88.2%.